Event‐related potentials during the ultimatum game in people with symptoms of depression and/or social anxiety - Nicolaisen‐Sobesky, Eliana; Paz, Valentina; Cervantes‐Constantino, Francisco; Fernández‐Theoduloz, Gabriela; Pérez, Alfonso; Martínez‐Montes, Eduardo; Kessel, Dominique; Cabana, Álvaro; Gradin, Victoria B. (Psychophysiology, 2023)
Depression and social anxiety are common disorders that have a profound impact on social functioning. The need for studying the neural substrates of social interactions in mental disorders using interactive tasks has been emphasized. The field of neuroeconomics, which combines neuroscience techniques and behavioral economics multiplayer tasks such as the Ultimatum Game (UG), can contribute in this direction. We assessed emotions, behavior, and Event‐Related Potentials in participants with depression and/or social anxiety symptoms (MD/SA, n = 63, 57 females) and healthy controls (n = 72, 67 females), while they played the UG. In this task, participants received fair, mid‐value, and unfair offers from other players. Mixed linear models were implemented to assess trial level changes in neural activity. The MD/SA group reported higher levels of sadness in response to mid‐value and unfair offers compared to controls. In controls, the Medial Frontal Negativity associated with fair offers increased over time, while this dynamic was not observed in the MD/SA group. The MD/SA group showed a decreased P3/LPP in all offers, compared to controls. These results indicate an enhanced negative emotional response to unfairness in the MD/SA group. Neural results reveal a blunted response over time to positive social stimuli in the MD/SA group. Moreover, between‐group differences in P3/LPP may relate to a reduced saliency of offers and/or to a reduced availability of resources for processing incoming stimuli in the MD/SA group. Findings may shed light into the neural substrates of social difficulties in these disorders. It is crucial to study the neural substrates of social interactions in mental health using interactive tasks that immerse the participant in a social context. The Ultimatum Game was used to assess ERPs to fair, mid‐value, and unfair offers from others in depressed and/or socially anxious volunteers. We found blunted neural responses over time to fair offers as well as reduced availability of resources for processing incoming social stimuli in depression and social anxiety.